2022
DOI: 10.3390/jcm11164662
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health in Breast Cancer Women with Vitamin D Deficiency: A Machine Learning Study

Abstract: Breast cancer (BC) survivors treated with aromatase inhibitors (AIs) commonly show several pathological issues, including poor oral health, bone health impairment, and vitamin D deficiency. However, to date, oral health issues in BC survivors treated with AIs have been poorly investigated and their relationship with vitamin D deficiency are far from being understood. This study aimed to evaluate the correlation between oral health and vitamin D status in BC survivors undergoing treatment with AIs through a mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Because of concerns over possible adverse effects of long-term bisphosphonate therapy (i.e., osteonecrosis of the jaw and atypical fractures), the need to continue treatment should be reviewed at regular intervals and the therapeutic treatment should be personalized on patients individual risk [ 149 ]. Indeed, it is crucial that an adequate screening of oral health status through a dentistry evaluation in high-risk subjects is carried out before administering anti-osteoporosis drugs [ 150 , 151 ]. In addition, these drugs might be commonly associated with adverse effects, including gastrointestinal problems, bowel disturbance, headache and musculoskeletal pain [ 152 ].…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…Because of concerns over possible adverse effects of long-term bisphosphonate therapy (i.e., osteonecrosis of the jaw and atypical fractures), the need to continue treatment should be reviewed at regular intervals and the therapeutic treatment should be personalized on patients individual risk [ 149 ]. Indeed, it is crucial that an adequate screening of oral health status through a dentistry evaluation in high-risk subjects is carried out before administering anti-osteoporosis drugs [ 150 , 151 ]. In addition, these drugs might be commonly associated with adverse effects, including gastrointestinal problems, bowel disturbance, headache and musculoskeletal pain [ 152 ].…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…However, there is still a lack of consensus about the precise identification of patients at higher risk, and there are no effective predictive tools to focus resources on rehabilitation plans to prevent BCRL, reducing its disabling consequences in BC survivors [26]. In this scenario, growing attention has been recently raised to machine learning solutions in BC management, with promising implications in developing self-improving technological models to guide clinicians in a precision medicine approach [28]. Interestingly, in 2018, Fu et al [29] realized and validated a real-time diagnostic tool for BCRL, assessing the most common symptoms mentioned by BCRL patients.…”
Section: Introductionmentioning
confidence: 99%
“…It’s showed a significant correlation between DMFT and vitamin D levels; the regression machine learning model showed that vitamin D status and the use of dental floss were the most relevant variables in terms of correlation with Filled Permanent Teeth Index (DMFT). Vitamin D deficiency, inadequate use of dental floss have a negative impact on oral health in BC women ( 17 ).…”
Section: Introductionmentioning
confidence: 99%